Politeness Strategies of Chinese in A Talk Show “If You Are The One” - Wu, Meimei; Wang, Jianning (European Publisher, 2019)
Based on discourse of a Chinese talk show, this study aims to test and verify Brown & Levinson’s (hereafter B&L) theory of politeness. Politeness is culture specific, and in this respect, the term of “face” provides more evidence. Adopting descriptive text analysis, this study analysed the transcriptions of a popular Chinese TV show If You Are the One on a rhetorical level in the context of Chinese culture. The present study reveals that politeness strategies are prevalent in If You Are the One, with the majority of them being positive politeness strategies, which contradict with B&L’s claim that people tend to select negative politeness as their preference, while bald on-record and off-record ones occurring rarely among the texts. The result shows that B&L’s politeness model provides us directions about the affecting elements of Chinese interaction on its validity. Under positive politeness, the author added three subcategories, namely speaking, “approbation of L”, “showing gratitude”, and “saving face for L”. The original typology presented by B&L may reflect a western cultural bias, but necessitating validation efforts for each culture is research worthy. Chinese peculiar culture contributes a lot to the result, which hints a further research in the future.